Suitability of Placental Blood Samples of Newborns for Pre-Transfusion Testing - Alissa, Rana; Williams, Patty D.; Baker, Erika L.; Hipp, Jennifer A.; Saremian, Jinous; Aysola, Agnes E. (Frontiers in Pediatrics, 2021)
OBJECTIVE: To show concordance between heel stick and placental blood sample pairs for newborns’ pre-transfusion testing, and to validate placental blood’s tube and gel methodology. METHODS: Placental samples were collected for pre-transfusion testing at birth from 78 singleton and twin newborns admitted to our Mother-Baby unit to compare with the results of heel stick samples taken from same newborns. Gestational age ≥ 35 weeks, weight ≥ 2000g. The study was approved by Institutional Review Board. Informed consent obtained from Newborn parents. ABO blood group, Rhesus factor (Rh), direct antiglobulin test (DAT) and antibody screen were performed. Ortho ProVue Analyzer used for tube and gel methods. McNemar’s test for paired categorical data was performed. RESULTS: 100% concordance in 78 pairs for ABO and Rh. 74 pairs tested for antibodies, 72 were both negative, one was both positive, one gave discordant result. 99% concordance p=0.999. 65 pairs were both DAT negative, seven were both DAT positive, six gave discordant results. 92% concordance. p=0.68. Placental blood gave identical results comparing tube with gel methods. CONCLUSIONS: Placental blood is suitable for pre-transfusion testing and can replace heel sticks. Placental blood tube and gel methods are validated.